The Conflict of Principles in Philosophical Disputes (Socrates’ polemics with the Sophists in Plato’s Gorgias) - Stoškus, Krescencijus (Problemos, 1974)
On the basis of the analyses of Socrates’ polemics with the sophists and orators an attempt is made to disclose the meaning and significance of such disputes in which opposite philosophical principles are being confronted justifying different modes of life, different hierarchies of values and yet from the viewpoint of their immediate consequences are quite inefficient. The author sees the meaning and significance of such disputes in the effect they exercise on the further development of respective philosophical principles, ideas and conceptions and, finally, on the philosophical thought proper as an independent sphere of the intellectual culture of a society.